Evaluation of BSF Larva Meal and Oil as White Shrimp Feed on Growth Performance, Body Composition, and Health Response - Rizal, Muhammad; Astuti, Dewi Apri; Fahmi, Melta Rini (Jurnal Perikanan Universitas Gadjah Mada, 2024)
The goal of this study was to evaluate the use of BSF larvae meal and oil as feed components in order to determine their impact on Litopenaeus vannamei shrimp growth performance, nutritional composition, and health response. Three shrimp ponds, each with a diameter of 20 m, were stocked with 72.000 Litopenaeus vannamei post larvae (PL-8), resulting in a stocking density of 229 shrimp per square meter. The trial diets comprised three types: control diet (K), diet containing BSF larvae meal (A), and diet containing BSF larvae meal plus oil (B). The parameters observed in this study included shrimp growth and productivity, feed consumption, feed conversion ratio (FCR), survival rate, nutritional composition (proximate, amino acid profile and fatty acid profile), total bacteria in the shrimp's digestive tract, and total hemocyte count in the shrimp's hemolymph. It was found that subtituting fish meal with 34% BSF larvae meal did not affect the growth performance of shrimp raised in shrimp ponds, compared to the control treatment. The assessment of the amino acid profile has revealed minimal variation between treatment. Nevertheless, both treatments A and B exhibited a decreased concentration of unsaturated fatty acids, specifically omega-3 and omega-6, in comparison to control. Meanwhile, treatment B had the highest levels of saturated fatty acid and omega-9 fatty acid content.